2021
DOI: 10.4103/jfmpc.jfmpc_2437_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the knowledge, preferences and concern regarding the prospective COVID-19 vaccine among adults residing in New Delhi, India – A cross-sectional study

Abstract: Background: Understanding the perception and concerns of people about COVID-19 vaccine in developing and populous country like India will help in understanding demand for the vaccine and further tailoring out public health information and education activities. The study was carried out to assess the present state of knowledge people have about the probable vaccine for COVID-19, to know the preferences of respondents about this vaccine and to learn the expectations and apprehensions of people about… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…After excluding each study and calculating the overall estimation, the pooled prevalence rate was unchanged (26.5%, 95% CI [22,31]). Danabal et al, 2021− Dara et al, 2021− Godasi et al, 2021− Goruntla et al, 2021− Hossain, Rana, et al, 2021− Islam, Agarwalla, et al, 2021− Islam, Siddique, et al, 2021− Jacob et al, 2021…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…After excluding each study and calculating the overall estimation, the pooled prevalence rate was unchanged (26.5%, 95% CI [22,31]). Danabal et al, 2021− Dara et al, 2021− Godasi et al, 2021− Goruntla et al, 2021− Hossain, Rana, et al, 2021− Islam, Agarwalla, et al, 2021− Islam, Siddique, et al, 2021− Jacob et al, 2021…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…A study was conducted among healthcare workers nationwide, which revealed that 84.1% of them accepted the vaccine, as they trusted the initiative by the government of India and the data from previous research [ 26 ]. In another study, studies were conducted on healthcare workers, and more than 50% of healthcare workers in Delhi were acquiescent to the vaccine, and 72% felt that immunisation should first be provided to front-line workers [ 20 ]. Kaur A. et al assessed the acceptance of the COVID-19 vaccine, and some participants (45.5% dental and 48.4% medical) expressed worry about unanticipated vaccination side effects.…”
Section: Discussionmentioning
confidence: 99%
“… Acceptance of the COVID-19 vaccine in India according to residence, as shown in the form of a forest plot [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. …”
Section: Figurementioning
confidence: 99%
“…Regionally, India has reported 63% to 80% acceptance. 17 , 18 In Bangladesh the vaccine acceptance ranged from 61% to 79%. 19 , 20 In both the countries the acceptance has increased over time.…”
Section: Discussionmentioning
confidence: 99%